Filamentous nestin and nonmuscle myosin IIB are associated with a migratory phenotype in neonatal rat cardiomyocytes. Issue 2 (11th July 2020) - Bergeron, Alexandre; Brezai, Andra; Shukr, Rami; Villeneuve, Louis; Allen, Bruce G.; Qureshi, Wasay M. S.; Hentges, Kathryn E.; Calderone, Angelino
Abstract: Cardiomyocyte migration represents a requisite event of cardiogenesis and the regenerative response of the injured adult zebrafish and neonatal rodent heart. The present study tested the hypothesis that the appearance of the intermediate filament protein nestin in neonatal rat ventricular cardiomyocytes (NNVMs) was associated in part with the acquisition of a migratory phenotype. The cotreatment of NNVMs with phorbol 12, 13‐dibutyrate (PDBu) and the p38α/β mitogen‐activated protein kinase inhibitor SB203580 led to the de novo synthesis of nestin. The intermediate filament protein was subsequently reorganized into a filamentous pattern and redistributed to the leading edge of elongated membrane protrusions translating to significant lengthening of NNVMs. PDBu/SB203580 treatment concomitantly promoted the reorganization of nonmuscle myosin IIB (NMIIB) located predominantly at the periphery of the plasma membrane of NNVMs to a filamentous phenotype extending to the leading edge of elongated membrane protrusions. Coimmunoprecipitation assay revealed a physical interaction between NMIIB and nestin after PDBu/SB203580 treatment of NNVMs. In wild‐type and heterozygous NMIIB embryonic hearts at E11.5–E14.5 days, nestin immunoreactivity was identified in a subpopulation of cardiomyocytes elongating perpendicular to the compact myocardium, at the leading edge of nascent trabeculae and during thickening of the compact myocardium. In mutant embryonic hearts lacking NMIIB protein expression, trabeculae formation was reduced, the compact myocardium significantly thinner and nestin immunoreactivity undetectable in cardiomyocytes at E14.5 days. These data suggest that NMIIB and nestin may act in a coordinated fashion to facilitate the acquisition of a migratory phenotype in neonatal and embryonic cardiomyocytes. Abstract : The appearance of filamentous nestin and nonmuscle myosin IIB (NMIIB) in neonatal rat ventricular cardiomyocytes led to the acquisition of a migratory phenotype. In the embryonic mouse heart, nestin was detected in a subpopulation of cardiomyocytes migrating outward from the compact myocardium and at the leading edge of nascent trabeculae. In embryonic mice lacking NMIIB, the impaired cardiogenic response was associated with a concomitant loss of nestin expression in cardiomyocytes.